Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1007/s004670050082
|View full text |Cite
|
Sign up to set email alerts
|

Girls prone to urinary infections followed into adulthood. Indices of renal disease

Abstract: This study describes blood pressure and renal function, as well as indices of renal disease, in females with and without renal scarring followed from their first urinary tract infection (UTI) in childhood. Of the 111 patients with a median follow-up time of 15 years, 54 had renal scarring (reflux nephropathy) on urography, which was severe in 19 and moderate in 35. The glomerular filtration rate was lower in patients with severe renal scarring and correlated with renal area on urography. However, the filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…A study of women with scarring using DMSA confirmed that renal function was reasonably well preserved and that the incidence of hypertension was lower than had previously been reported. 27 …”
Section: Discussionmentioning
confidence: 99%
“…A study of women with scarring using DMSA confirmed that renal function was reasonably well preserved and that the incidence of hypertension was lower than had previously been reported. 27 …”
Section: Discussionmentioning
confidence: 99%
“…115 Removal of a scarred kidney when the contralateral kidney is thought to be normal does not, however, always cure hypertension. 63 Moreover, differential renal vein renin activity measurements in hypertensive patients with unilateral scarring may not localise the increased renin release to the scarred kidney and attention must therefore be paid to the PRA in the renal vein of the radiologically normal kidney.…”
Section: Managementmentioning
confidence: 99%
“…It has been shown that adults with persistent reflux and scarring may run the risk of further pyelonephritis, progressive renal disease and hypertension [Martinell et al 1996[Martinell et al , 1995, and VUR is likely a major factor in the pathogenesis of recurrent UTI, acute pyelonephritis and renal scarring [Faust et al 2009]. Thus, the aims of treatment are to reduce the risk of febrile UTIs affecting the upper urinary tract and, possibly, protect against future renal damage.…”
Section: Introductionmentioning
confidence: 99%